Characterization of human rotavirus serotype G9 isolated in Japan and Thailand from 1995 to 1997 - Zhou Y. (2014)
Serotyping of human rotavirus was conducted in 396 Japanese and 100 Thai rotavirus-positive fecal specimens collected from 1995 to 1997. Serotype G9 was found to be the third most common serotype with frequency of 16.2% in Thailand from 1996 to 1997. It was also detected in Japan with a low frequency (0.7%) in this year. The genetic analyses of VP4 and NSP4 genes of these G9 strains showed that 1 strain from Japan possessed P[8] genotype and NSP4 Wa-group with long electropherotpe (e-type). In contrast, 5 strains from Thailand belonged to P[6] and 1 strain belonged to P[4]. All of the Thai strains were in the NSP4 KUN-group with a short e-type. Sequence analysis of their VP7 gene revealed that there was the highest homology among fecal G9 strains (>96.3%, amino acid identity) and a relatively high degree of homology to standard viruses, F45 from Japan (95.4-96.3%, amino acid identity) and 116E from India (92-92.3%, amino acid identity). However, immunological analysis using G9 specific monoclonal antibodies (Mabs) against VP7 protein showed that the G9 strains isolated from the two countries had different antigenic specificity. It was confirmed further by intraserotypical phylogenetic analysis of VP7 amino acid. These results indicated that the prevalence of G9 rotavirus in 1996-1997 in Thailand was relative to the continuing recent emergence of it on a worldwide basis, while the Japanese G9 strain isolated in this survey was identified to have progenitors common to the F45 strain that was prevalent in 1985 in Japan. Phylogenetic analysis of VP7 amino acid of G1-14 prototype rotavirus showed that the G9 strains were most closely related to the equine G14 rotavirus F123 strain but G3 strains, interserotypically. These findings suggest that G9 rota-viruses might be divided into two or more subtypes. © 2001 Wiley-Liss, Inc.